Between Policy and Reality, an Evaluation of Swiftlet Nest Tax Implementation in Hulu Sungai Utara, South Kalimantan - Agus Surya Dharma; Rudy Handoko; Achluddin Ibnu Rochim (Cita konsultindo, 2026)
This study evaluates the swiftlet nest tax policy in Hulu Sungai Utara Regency, South Kalimantan, Indonesia, focusing on its effectiveness in increasing Original Local Revenue (PAD). Despite the high economic potential of the swiftlet sector, its contribution to PAD remains below 1%, revealing a gap between potential and fiscal realization. Using a qualitative descriptive approach, data were collected through in-depth interviews and focus group discussions with 19 key informants, complemented by document analysis of regional regulations. The evaluation employs William N. Dunn’s policy criteria effectiveness, efficiency, adequacy, equity, and responsiveness along with George C. Edward III’s implementation theory. Findings indicate that the policy is administratively compliant but substantively ineffective. Low taxpayer compliance, weak supervision, inadequate monitoring, and insufficient risk-based instruments hinder revenue optimization. Efficiency and adequacy are limited, the distribution of tax burdens is inequitable, and responsiveness remains procedural rather than adaptive. The study suggests that sustainable improvement of PAD requires an integrated, adaptive, and policy-learning-oriented approach. This includes data-based governance, risk-focused monitoring, equitable taxpayer treatment, and periodic evaluation to align policy instruments with sector characteristics. The research provides a conceptual and practical framework for enhancing local fiscal policy in high-potential but underperforming sectors.